Health Seeking Behavior by Thai Herbal Consumption of Older Adults During COVID - 19 Pandemic Situation in Surat Thani Province - Bunkongthong, Panida; Thanapop, Sasithorn; Saisanan Na Ayudhaya, Wanvisa (Princess of Naradhiwas University Journal, 2025)
The descriptive study aimed to determine relationship related to predisposing, enabling, and reinforcing factors as well as health seeking behavior by Thai herbal consumption of older adults during COVID - 19 pandemic situation in Surat Thani province. Methods: a descriptive cross-sectional study, 367 community-dwelling older adults between April and June of 2023 provided data via a questionnaire whose content validated between 0.67 and 1.00 and its reliability was 0.89. Data was analyzed by using descriptive statistics and chi-square statistics. Results: The majority of older adults (63.76 %) were female, aged 60 - 69 years (57.76 %), had no underlying diseases (63.76 %), had completed primary school (63.21 %), were married (65.12), had used herbs (76.29 %), had a high level of knowledge about consuming Thai herbs (79.84 %), a moderate level of attitude (50.69 %), a high level of perceived benefit (59.67 %), and a moderate level of health seeking behavior (46.05 %). Predisposing, enabling, and reinforcing factors were associated with the health seeking behavior of older adults who consumed Thai herbs. Based on the findings, families and community health care providers should educate people about the proper use of Thai herbs as a substitute for traditional medical care in the event that access to primary healthcare is restricted due to a pandemic of infectious diseases.